2011
DOI: 10.1097/bot.0b013e3181d7a3a6
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Comparison of Locking versus Nonlocking Volar and Dorsal T-Plates for Fixation of Dorsally Comminuted Distal Radius Fractures

Abstract: No difference in all measured biomechanical parameters supports equivalence between constructs and surgeon discretion in determining operative method. Minimal fragment displacement and construct deformation during physiological testing support previous data that early postoperative motion can be recommended. Fragment displacement that occurs does so in the early periods of motion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 34 publications
2
18
0
1
Order By: Relevance
“…This mode of failure has been observed following mechanical testing of elderly cadavera with fractures of the distal radius. (16,25) The values of stiffness under axial compression and loads to catastrophic failure obtained in this study were similar to those observed in elderly cadaveric models, further supporting the validity of our Sawbone model (Table 3). (13,16,25) While models such as the fourth generation Sawbones (Pacific Research Labs, Vashon, WA) have excellent reliability and uniform mechanical properties, they are manufactured to be comparable to young adult diaphyseal bone.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…This mode of failure has been observed following mechanical testing of elderly cadavera with fractures of the distal radius. (16,25) The values of stiffness under axial compression and loads to catastrophic failure obtained in this study were similar to those observed in elderly cadaveric models, further supporting the validity of our Sawbone model (Table 3). (13,16,25) While models such as the fourth generation Sawbones (Pacific Research Labs, Vashon, WA) have excellent reliability and uniform mechanical properties, they are manufactured to be comparable to young adult diaphyseal bone.…”
Section: Discussionsupporting
confidence: 74%
“…(12,15,(17)(18)(19)(20)(21)(22)(23)(24) Gondusky et al and Weninger et al identified in prior distal radius mechanical testing that all changes attributable to cyclic loading occurred in the first 200-500 cycles, thus we deemed 1,000 cycles sufficient to condition the constructs. (11,(13)(14)(15)(16) Destructive testing was completed to determine load (N) to clinical failure which was defined as 2mm of displacement at the osteotomy gap, (10) and subsequent catastrophic failure, defined as complete closure of the 1 cm osteotomy gap and or fracture.…”
Section: Biomechanical Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant controversy exists about whether dorsal or volar plating is superior for fixation of dorsally comminuted distal radial fractures [1113]. …”
Section: Discussionmentioning
confidence: 99%
“…In a biomechanical study on dorsally comminuted extra-articular distal radial fractures comparing dorsal T-plate with volar locking plate, it was inferred that there was no difference in any of the biomechanical parameters, namely, stiffness, fragment displacement at 500 cycle-intervals, and axial load to failure between these constructs [13]. …”
Section: Discussionmentioning
confidence: 99%